Immunohistochemistry pattern of hepatic inflammatory and insulin resistance markers in experimental model of nonalcoholic steatohepatitis - Mônica Souza de Miranda Henriques; Jacqueline Alves Leite; Margareth de Fátima Formiga de Melo Diniz; Maria Salete Trigueiro de Araújo (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction:The pathophysiology of nonalcoholic steatohepatitis (NAS) includes, basically, insulin resistance, inflammation and oxidative stress. Thus, a study of immunostaining for liver insulin, adiponectin, tumor necrosis factor alpha (TNF-α), and inducible nitric oxide synthase (iNOS) receptors was conducted.Objective:To expand the knowledge about the pathophysiological and molecular mechanisms underlying the experimental model of steatohepatitis in rats fed a high-fat diet.Method:Twenty Wistar rats were divided into two groups: G1 (control, fed a standard diet), and G2 (fed a high-fat diet containing 58% of energy derived from fat, 18% from protein and 24% from carbohydrate). After eight weeks the animals were sacrificed. Blood glucose, insulin, total cholesterol, high-density lipoprotein (HDL), the very low-density lipoproteins (VLDL), triglycerides, aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and gamma-glutamyl transferase (GGT) were determined. The liver tissue was submitted to histopathological analysis, using a NAS score. In immunohistochemistry, we studied the expression of the insulin receptor, adiponectin, TNF-α and iNOS by tissue microarray method.Results and conclusion:There was marked cytoplasmic immunostaining for TNF-α and iNOS mediators in the group on a fat diet. Regarding insulin and adiponectin molecular markers, a reduction of cytoplasmic immunoreactivity of these antigens was observed in the group on a fat diet, reflecting, respectively, the state of hepatocellular inflammation (steatohepatitis) and insulin resistance in this experimental model of fat liver disease.